Fast and slow Ca2+-dependent hyperpolarization mechanisms connect membrane potential and sleep homeostasis. (June 2017) - Ode, Koji L; Katsumata, Takahiro; Tone, Daisuke; Ueda, Hiroki R
Highlights: Cortical neurons may have an intrinsic ability to initiate a slow firing rhythm. The cortical firing pattern may actively regulate sleep and wake states. Ca 2+ -dependent hyperpolarization may control rhythmic firing. Ion channels and kinases involved in Ca 2+ signaling regulate sleep duration. Sleep-regulating kinases may act on ion channels to achieve sleep homeostasis. Abstract : Several lines of evidence indicate that the sleep-wake state of cortical neurons is regulated not only through neuronal projections from the lower brain, but also through the cortical neurons' intrinsic ability to initiate a slow firing pattern related to the slow-wave oscillation observed in electroencephalography of the sleeping brain. Theoretical modeling and experiments with genetic and pharmacological perturbation suggest that ion channels and kinases acting downstream of calcium signaling regulate the cortical-membrane potential and sleep duration. In this review, we introduce possible Ca 2+ -dependent hyperpolarization mechanisms in cortical neurons, in which Ca 2+ signaling associated with neuronal excitation evokes kinase cascades, and the activated kinases modify ion channels or pumps to regulate the cortical sleep/wake firing mode.